Liquid Chromatographic Method for the Analysis of Brimonidine in Ophthalmic Formulations. Issue 3 (2012) - Narendra, A.; Deepika, D.; Annapurna, M. Mathrusri
Abstract : A reverse phase LC method was developed for the determination of Brimonidine in eye drops. Chromatography was carried on an Inertsil ODS 3V column (C18) using a mixture of Octane 1- sulfonic acid sodium salt (0.02M) (pH 3.5 ± 0.05) and acetonitrile (64:36 v/v) as mobile phase at a flow rate of 1 mL/min with UV detection at 254 nm. The drug was eluted at 4.636 min. The detector response was linear in the concentration range of 0.4–72 μg/mL. The limit of detection and limit of quantification were found to be 0.0561 and 0.1848 μg/mL respectively. The proposed method was validated as per the ICH guidelines and can be applied for the routine analysis of Brimonidine in eye drops.